Parasitization of the white rice stem bore< Scirpophaga innotata (Walker) (Lepidoptera: Pyralidae), was studied in Karawang during an outbreak in 1991/1992. The percentage of egg masses parasitized averaged 85.5%, whereas the percentage of individual eggs parasitized 44.2%. Egg masses attacked by parasitoids yielded 1 to 100 wlth arz average of 53.9 borer larvae. A mean of 56.6parasitoid wasps emerged from the parasitized egg masses. Based on the proportion of egg masses parasitized and the numb - Aunu Rauf (Buletin Hama dan Penyakit Tumbuhan, 2000)
Parasitization of the white rice stem bore< Scirpophaga innotata (Walker) (Lepidoptera: Pyralidae), was studied in Karawang during an outbreak in 1991/1992. The percentage of egg masses parasitized averaged 85.5%, whereas the percentage of individual eggs parasitized 44.2%. Egg masses attacked by parasitoids yielded 1 to 100 wlth arz average of 53.9 borer larvae. A mean of 56.6parasitoid wasps emerged from the parasitized egg masses. Based on the proportion of egg masses parasitized and the number of wasps emerged, the predominant parasitoid was Telenomus rowani Gahan, followed by Trichogramma japonicum Ashmead, and the least was Tetrastichus schoenobii Ferriere. The level of individual egg parasitization was 22.7% for T. japonicum 55.8% for T. rowani, and 92.1% for T. schoenobii. A mean of 66.5 borer larvae survived after attack by T. japonicum, 19.4 lawae by T. rowani, and only 0.8 larvae per egg mass by T. schoenobii. The last mentioned species was the most efJicient and efective parasitoid, and the borer outbreak was considered to be related to the low level of eggparasitization by T. schoenobii.